Towards industrial implementation of glycine-based leach and adsorption technologies for gold-copper ores - Eksteen, Jacques; Oraby, E.; Tanda, B.; Tauetsile, P.; Bezuidenhout, G.; Newton, T.; Trask, F.; Bryan, I. (Maney Publishing, 2017)
© 2017 Canadian Institute of Mining, Metallurgy and Petroleum The technology to selectively leach gold, silver and base metals from ores, concentrates, and wastes, using an alkaline glycine solution, has initiated significant interest in using the new technology in various environments such as in situ, in-place, dump, heap, and vat and agitated tank leaching. It has been shown that glycine acts synergistically with a number of other lixiviants to lower the net consumption of the other lixiviants while allowing low-cost glycine solution recovery. Glycine is a non-toxic, stable, environmentally benign reagent that is available in bulk industrial quantities. It has the ability to dissolve most copper oxide and sulphide minerals, as well as native copper, whilst not interacting with acid-consuming gangue nor dissolving iron and various or ubiquitous gangue elements. It acts synergistically with small amounts of cyanide to leach gold-copper ores at leach rates higher than either glycine or cyanide on their own, while significantly reducing cyanide consumption and eliminating detoxification requirements. The leaching behaviour of various glycine-based systems will be reviewed, followed by the evaluation of the adsorption of gold onto activated carbon. Where the economics merit it, copper can be easily recovered using solvent extraction or sulphide precipitation.